2017
DOI: 10.1002/2016gb005613
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Dominance of N2 Fixation in the North Atlantic Ocean

Abstract: To investigate the controls on N2 fixation and the role of the Atlantic in the global ocean's fixed nitrogen (N) budget, Atlantic N2 fixation is calculated by combining meridional nitrate fluxes across World Ocean Circulation Experiment sections with observed nitrate 15N/14N differences between northward and southward transported nitrate. N2 fixation inputs of 27.1 ± 4.3 Tg N/yr and 3.0 ± 0.5 Tg N/yr are estimated north of 11°S and 24°N, respectively. That is, ~90% of the N2 fixation in the Atlantic north of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 96 publications
(168 reference statements)
4
67
0
Order By: Relevance
“…The Atlantic Ocean, which is the most studied ocean basin (Figure ), displays a small coefficient of variation (CV) among models (Figure b). In contrast to the subtropical oceans, the equatorial Atlantic is estimated to harbor intense N 2 fixation rates, consistent with some of the field observations and geochemical estimates (Marconi et al, ; Montoya et al, ; Snow et al, ). However, these hot spots are not consistently identified in all models (e.g., Gulf of Guinea and northeast Atlantic with relatively large CV).…”
Section: Discussionsupporting
confidence: 83%
“…The Atlantic Ocean, which is the most studied ocean basin (Figure ), displays a small coefficient of variation (CV) among models (Figure b). In contrast to the subtropical oceans, the equatorial Atlantic is estimated to harbor intense N 2 fixation rates, consistent with some of the field observations and geochemical estimates (Marconi et al, ; Montoya et al, ; Snow et al, ). However, these hot spots are not consistently identified in all models (e.g., Gulf of Guinea and northeast Atlantic with relatively large CV).…”
Section: Discussionsupporting
confidence: 83%
“…The use of World Ocean Atlas fields for this fixed N input function (examined closely by Martin et al, ) vastly simplifies the computational requirements of the model and allows us to focus on other aspects of the N cycle with this model. Our model parameterization yields a global N 2 fixation rate of 131 Tg N/year, which is similar in magnitude to estimates from both regional and global modeling and observational studies (Table S4; Deutsch et al, ; Luo et al, ; Fonseca‐Batista et al, ; Marconi et al, ). A fixed δ 15 N value (−1‰) was also assumed for newly fixed N (Carpenter et al, ; Hoering & Ford, ).…”
Section: Methodssupporting
confidence: 77%
“…Closer inspection of the Atlantic using depth and zonally averaged sections (Figs. 5 and 6) revealed that the model adequately reproduced the low δ 15 N signature of N 2 fixation at ∼4 ‰ occurring in the tropical Atlantic (Marconi et al, 2017). We found a total, basin-wide rate of Atlantic N 2 fixation equal to ∼33 Tg N yr −1 .…”
supporting
confidence: 57%